Situation Report: Romania, 19 June 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Konstantin Katushev Receives Romanian Ambassador Central Committee to Meet Grand National Assembly to Meet on June 20 Further Drop in "Socialist" Countries' Share in Romanian Foreign Trade in 1967 Apostol to Italy Mihai Dalea to Iceland Economic News Miscellaneous